El clima organizacional y su relación con el desempeño laboral del personal del área de recursos humanos de un outsourcing internacional en el año 2017 - Goicochea, Diana Carolina (2019)
This research carried out, it arose due the interest and necessity of looking for improve organizational climate and through this variable improve too laboral performance with the purpose of improve the competitive situation in local level and also in international market, in order to continue with the process of international expansion in markets that we are consolidated and also the possibility to explorer new markets and attract clients. In this research carried out, it is proposed to investigate factors that affect the correct laboral performance and the normal development of functions, starting from the perspective of organizational climate. The research carried out was no experimental, descriptive correlational. For this research applied a survey wuit 46 questions, this survey allowed the collection and analysis of data, for that it was used the scale of Likert applied to 62 people randomly selected. The object of the study was the staff of Human Resources in an international outsourcing in 2017 In the development of research, we verify the factor that influence in organizational climate that finally applied influence in laboral performance. This research is elaborated with the purpose of achieve improve the laboral performance of workers through the development of organizational climate, this improve is looking for the possibility of introduce our services in new international markets.